Zane and the Hurricane : a Story of Katrina - Philbrick, W. R. (W. Rodman) (New York : The Blue Sky Press, an imprint of Scholastic Inc., 2014)
A twelve-year-old boy and his dog become trapped in New Orleans during the horrors of Hurricane Katrina.
Keywords: Hurricane Katrina, 2005 -- Juvenile fiction; Survival -- Juvenile fiction; Racially mixed people -- Juvenile fiction; African Americans -- Juvenile fiction; Hurricane Katrina, 2005 -- Fiction; Survival -- Fiction; Racially mixed people -- Fiction; African Americans -- Fiction; New Orleans (La.) -- Juvenile fiction; New Orleans (La.) -- Fiction